PENERAPAN RESTORATIVE JUSTICE TINDAK PIDANA KORUPSI DENGAN NOMINAL KECIL DALAM SISTEM PERADILAN PIDANA DI INDONESIA - Mudrika, Mudrika; Sriwidodo, Joko; Dewi, Diah Sulastri (LPPM Institut Pendidikan Nusantara Global, 2023)
The research results explain that strong, consistent, and non-discriminatory law enforcement is a key element in ensuring the existence of principles of justice and legal certainty. It also has the potential to benefit society through deterrence, which can discourage individuals from engaging in corruption. Additionally, it contributes to building public trust in law enforcement efforts and law enforcement agencies. Consequently, public support for law enforcement institutions is strengthened. The development of this concept in anti-corruption law is expected to help recover state losses caused by corruption. Moreover, this punitive concept also offers several benefits in achieving the objectives of penalizing offenders. With a clear obligation to repay restitution without compromise, an offender will work under state supervision to generate funds used to cover the losses resulting from their actions.